Digital Transformation in TV Broadcasting Management: Case Study in Southeast Asia - Yuningsih, Siti Hadiaty; Surya, Dhika (Communication In Research And Publications, 2025)
Digital transformation has fundamentally changed television broadcasting management in Southeast Asia. This study examines two countries, Indonesia and Malaysia, which are at different stages of digital adoption. A qualitative research method with a case study approach is used, combining an international literature review, policy documents, and semi-structured interviews with broadcast practitioners. Thematic and comparative analysis, framed by the Dynamic Capabilities Framework, uncovers three main aspects: (1) organizational restructuring and multi-platform strategies; (2) technology adoption including DVB-T2 infrastructure, IP-based production systems, and AI for content recommendation; and (3) business model innovation through digital revenue diversification (YouTube, programmatic advertising, and OTT). The results show that Malaysia benefits from centralized policies and early infrastructure readiness, while Indonesia still faces challenges of decoder ownership, regional digital divide, and legacy-new system integration. Both countries emphasize the importance of human resource training, public-private collaboration, and incentive policies to accelerate digital adoption. Recommendations for the study include strengthening dynamic organizational capabilities, funding innovation, and digital literacy programs for the community. These findings provide strategic guidance for stakeholders to optimize broadcasting management in the digital era, towards an inclusive, adaptive, and sustainable ecosystem.